Adolescent intermittent ethanol (AIE) produces sex specific alterations in adult neuroimmune gene expression and ethanol sensitivity that are independent of ethanol metabolism. (1st September 2021) - Vore, Andrew S.; Barney, Thaddeus M.; Gano, Anny; Varlinskaya, Elena I.; Deak, Terrence
Abstract: The goal of the present studies was to determine long-lasting effects of adolescent intermittent ethanol (AIE), a rodent model of binge patterns of ethanol consumption, on (i) behavioral sensitivity to ethanol challenge in adulthood using the Loss of Righting Reflex (LORR) test; (ii) ethanol pharmacokinetics and ethanol-metabolizing enzyme expression when re-challenged with ethanol as adults; and (iii) induction of neuroimmune gene expression during an adult binge-like ethanol challenge. To evaluate the impact of AIE on ethanol sensitivity in adulthood, adult rats received a sedative ethanol dose of 3.5 g/kg and were tested for the LORR. Sexually dimorphic effects were observed, with AIE males showing more rapid recovery than vehicle exposed controls, an effect that was completely absent in females. Rats exposed to the same AIE procedure were challenged with 0.75, 1.5, or 3.0 g/kg i.p. ethanol in adulthood. Female rats with a history of AIE displayed a small increase in ethanol clearance rate when challenged with 0.75 g/kg, however no other significant differences in ethanol pharmacokinetics were noted. To assess persistent AIE-associated changes in neuroimmune gene expression, rats were challenged with 0 or 2.5 g/kg ethanol. Both male and female adult rats with a history of AIE displayed sensitized hippocampal IL-6 and IκBα gene expression in response to ethanol challenge. Changes in cytokine gene expression as well as ethanol sensitivity assessed by LORR were not shown to be the result of changes in ethanol pharmacokinetics and point to AIE altering other mechanisms capable of significantly altering the neuroimmune and behavioral response to ethanol. Highlights: AIE exposure produces long lasting changes in the neuroimmune response to future ethanol challenge. AIE exposure results in long term changes in ethanol sensitivity assessed by LORR. Sexually dimorphic changes in ethanol metabolism genes and ethanol sensitivity were observed after a history of AIE.